Conditional Sentenses - Attala Rania Insyra Pasaribu; Riqqah Aprillia Wijaya; Yani Lubis (Cendekia Madani Nusantara, 2024)
This study dealt with the using of conditional sentences in delivering a message especially in a newspaper. The purposes of this study was to describe the conditional sentences that occurred in the opinion texts and to derive the dominant category of conditional sentences in delivering a message in a newspaper then to reasoning why it was actualized in the way it was. This study conducted by using descriptive method with a qualitative approach. The data of this study were the opinion texts from the daily newspaper of The Jakarta Post. Determining, identifying, and analyzing were the steps in analyzing the data. The findings of this research show that all the types of conditional sentences are used in delivering the message in the opinion texts in The Jakarta Post. The using of conditional type I is likely to 52,70%; type II is 14,19%; type III is 0,68% and 0 conditional is 32,43%. So from the findings it shows that the most dominant type that used in opinion texts in The Jakarta Post is conditional sentences type I. The findings of this study are very useful for the editors of newspaper in editing the news before it is printed. They need to know conditional sentences well in order to relate one clause to another clause in delivering the message so the information can be understood by the readers easily. By knowing the conditional sentences well it will be easier to know and to understand the message written down in the newspaper.